Memories of hell - Centre Productions; Barr Films (Irwindale, CA : Barr Films, 1982)
Features the recollection of former GI'S from New Mexico who survived the fall of the Philippines and the brutal Bataan death march. This documentary features rare footage and interviews with the survivors providing firsthand insights into World War II history.
VHS format.
"#V430."
Fernando Sanchez, Robert Maestas.
Keywords: World War, 1939-1945 -- Concentrations camps -- Philippines; World War, 1939-1945 -- Prisoners and prisons, Japanese; World War, 1939-1945 -- Prisoners and prisons, American; Prisoners of war -- Philippines